PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KUALITAS LABA DENGAN LEVERAGE SEBAGAI VARIABEL PEMODERASI - Noberto Nugroho Sitorus; Bertha Beloan; Frischa Faradila Arwinda Mongan; Maria Yessica Halik (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2022)
This study aims to determine the effect of corporate social responsibility disclosure on earnings quality with leverage as a moderating variable. The data in this study is secondary data in the form of annual reports and sustainability reports (CSR). The data was obtained from the IDX's official website and from each company that attached the data. Determination of the sample using the purposive sampling method with 79 samples of manufacturing companies from 2018-2020. The results of the analysis using t-test and f-test show that corporate social responsibility and leverage have a positive effect on earnings quality by 14.5%, and the rest is influenced by other factors.